The functional organization of corticomotor neurons within the motor cortex differs among basketball and volleyball athletes with patellar tendinopathy compared to asymptomatic controls - Vallance, P.; Kidgell, D. J.; Vicenzino, B.; Frazer, A. K.; Garofolini, A.; Malliaras, P. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Patellar tendinopathy (PT) typically affects jumping-sport athletes with functional impairments frequently observed. Alterations to the functional organization of corticomotor neurons within the motor cortex that project to working muscles are evident in some musculoskeletal conditions and linked to functional impairments. We aimed to determine if functional organization of corticomotor neuron projections differs between athletes with PT and asymptomatic controls, and if organization is associated with neuromuscular control. We used a cross-sectional design, and the setting was Monash Biomedical Imaging. Basketball and volleyball athletes with (n = 8) and without PT (n = 8) completed knee extension and ankle dorsiflexion force matching tasks while undergoing fMRI. We determined functional organization via identification of the location of peak corticomotor neuron activation during respective tasks (expressed in X, Y, and Z coordinates) and calculated force matching accuracy for both tasks to quantify neuromuscular control. We observed significant interactions between group and coordinate plane for functional organization of corticomotor projections to knee extensors (p < 0.001) and ankle dorsiflexors (p = 0.016). Compared to controls, PT group peak corticomotor activation during the knee extension task was 9.6 mm medial (p < 0.001) and 5.2 mm posterior (p = 0.036), and during the ankle dorsiflexion task 8.2 mm inferior (p = 0.024). In the PT group, more posterior Y coordinate peak activation location during the knee extension task was associated with greater task accuracy (r = 0.749, p = 0.034). Functional organization of corticomotor neurons differed in jumping athletes with PT compared to controls. Links between functional organization and neuromuscular control in the PT group suggest organizational differences may be relevant to knee extension neuromuscular control preservation.